A High-Fat Diet Exacerbates the Course of Experimental Trypanosoma cruzi Infection That Can Be Mitigated by Treatment with Simvastatin. (8th June 2020) - de Souza, Débora Maria Soares; de Paula Costa, Guilherme; Leite, Ana Luísa Junqueira; de Oliveira, Daniela Silva; de Castro Pinto, Kelerson Mauro; Farias, Sílvia Elvira Barros; Simões, Natália Figueiroa; de Paiva, Nívia Carolina Nogueira; de Abreu Vieira, Paula Melo; da Silva, Camilo Adalton Mariano; Figueiredo, Vivian Paulino; de Jesus Menezes, Ana Paula; et al.
Abstract : The protozoan Trypanosoma cruzi is responsible for triggering a damage immune response in the host cardiovascular system. This parasite has a high affinity for host lipoproteins and uses the low-density lipoprotein (LDL) receptor for its invasion. Assuming that the presence of LDL cholesterol in tissues could facilitate T. cruzi proliferation, dietary composition may affect the parasite-host relationship. Therefore, the aim of this study was to evaluate myocarditis in T. cruzi -infected C57BL/6 mice—acute phase—fed a high-fat diet and treated with simvastatin, a lipid-lowering medication. Animals (n = 10 ) were infected with 5 × 10 3   cells of the VL-10 strain of T. cruzi and treated or untreated daily with 20 mg/kg simvastatin, starting 24 h after infection and fed with a normolipidic or high-fat diet. Also, uninfected mice, treated or not with simvastatin and fed with normolipidic or high-fat diet, were evaluated as control groups. Analyses to measure the production of chemokine (C-C motif) ligand 2 (CCL2), interferon- (IFN-) γ, interleukin- (IL-) 10, and tumor necrosis factor (TNF); total hepatic lipid dosage; cholesterol; and fractions, as well as histopathological analysis, were performed on day 30 using cardiac and fat tissues. Our results showed that the high-fat diet increased (i) parasite replication, (ii) fat accumulation in the liver, (iii) total cholesterol and LDL levels, and (iv) the host inflammatory state through the production of the cytokine TNF. However, simvastatin only reduced the production of CCL2 but not that of other inflammatory mediators or biochemical parameters. Together, our data suggest that the high-fat diet may have worsened the biochemical parameters of the uninfected and T. cruzi -infected animals, as well as favored the survival of circulating parasites.